n-3 PUFAs reduce tumor load and improve survival in a NASH-tumor mouse model - Liebig, Marie (Ther Adv Chronic Dis, 2019)
BACKGROUND: With 9.1% of all cancer deaths, hepatocellular carcinoma is the second leading cause of cancer deaths worldwide. Due to the increasing prevalence of metabolic syndrome, nonalcoholic fatty liver disease (NAFLD) has evolved into a major risk factor for hepatocellular carcinoma development. Herein, we investigated whether a dietary n-3 polyunsaturated fatty acid (PUFA) supplementation improves the outcome of progressive NAFLD. METHODS: Feeding three high-fat diets, differing in n-3 and n-6 PUFA contents and ratios (n-3/n-6: 1:8, 1:1, 5:1), the impact of n-3 PUFAs and n-3/n-6 PUFA ratios on NAFLD-related liver fibrosis and tumorigenesis was analyzed in 12- and 20-week-old streptozotocin/high-fat diet (STZ/HFD)-treated mice. RESULTS: Feeding of n-3 PUFA-rich diets (1:1 and 5:1) resulted in increased hepatic n-3 PUFA content and n-3/n-6 PUFA ratio with decreased hepatic lipid accumulation. In 20-week-old mice, n-3 PUFA-rich diets alleviated tumor load significantly, with reduced liver/body weight index, tumor size, and tumor number. Finally, these effects were accompanied by a significant improvement of survival of these mice. CONCLUSIONS: Herein, we showed that increased n-3 PUFA content and n-3/n-6 PUFA ratios lead to improved survival and attenuated tumor progression in STZ/HFD-treated mice. Thus, n-3 PUFAs could be the basis for new therapeutic options against NAFLD-related tumorigenesis.